Sequence features indicate a positive net charge is influential for the sub-cellular localization of proteins in organisms with complex plastids. - Jeem, Fuad Sarker (Jihočeská univerzita, 2023)
Intracellular targeting of proteins in cells with complex plastids of red algal origin; the targeting signals of plastid proteins in these organisms are different from those in plants and other groups of algae. These signals should be characterized in comparison to proteins that are not targeted to the plastids.
Sequence features indicate a positive net charge is influential for the sub-cellular localization of proteins in organisms with complex plastids.
Keywords: Plastid; Signal peptide; Transit peptide; Diatoms; N-terminal; Secondary endosymbiosis; Plastid; Signal peptide; Transit peptide; Diatoms; N-terminal; Secondary endosymbiosis